Changing the paradigm of homelessness - Vissing, Yvonne Marie (Routledge, 2020)
Changing the Paradigm of Homelessness offers a comprehensive look at family housing distress related to the homelessness epidemic in the United States. This book explores the causes and consequences of this epidemic and proposes drastic changes in America's historically ill-fated approach to family homelessness. By describing this crisis in detail, the authors enlighten readers to the scope of this issue, describe those impacted by it, and outline ways to shift public policies and public perceptions. The authors interweave scholarly concepts with insights of those who are currently or previously homeless, and, in doing so, they show the importance of academic knowledge influencing policy decisions and the ways in which these influences impact the lives of real persons. This book, then, uses pedagogy, policy, and pragmatism to critique the United States' approach to family homelessness